2006
DOI: 10.1051/0004-6361:20065653
|View full text |Cite
|
Sign up to set email alerts
|

Probing the formation of intermediate- to high-mass stars in protoclusters

Abstract: Aims. The earliest phases of massive star formation in clusters are still poorly understood. Here, we test the hypothesis for high-mass star formation proposed in our earlier paper (Peretto et al. 2006) stating that a massive, ultra-dense core may be currently forming at the center of the collapsing NGC 2264-C protocluster via the gravitational coalescence of several intermediate-mass Class 0 objects. Methods. In order to confirm the physical validity of this hypothesis, we carried out IRAM Plateau de Bure int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
110
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(125 citation statements)
references
References 76 publications
(117 reference statements)
13
110
2
Order By: Relevance
“…The internal structure of NGC 2264-C and NGC 2264-D was subsequently resolved by higher-resolution millimeter and submillimeter studies Williams & Garland 2002;Peretto et al 2006Peretto et al , 2007. In particular, through 1.2 mm continuum observations, Peretto et al (2006) identified 12 compact dense cores in NGC 2264-C (see Fig.…”
Section: Our Target Region: Ngc2264-cmentioning
confidence: 99%
See 4 more Smart Citations
“…The internal structure of NGC 2264-C and NGC 2264-D was subsequently resolved by higher-resolution millimeter and submillimeter studies Williams & Garland 2002;Peretto et al 2006Peretto et al , 2007. In particular, through 1.2 mm continuum observations, Peretto et al (2006) identified 12 compact dense cores in NGC 2264-C (see Fig.…”
Section: Our Target Region: Ngc2264-cmentioning
confidence: 99%
“…The IRAM Plateau de Bure interferometer observations of Peretto et al (2007) revealed a thirteenth source, C-MM13, located only 13.5 (or ∼0.05 pc) away from C-MM3.…”
Section: Our Target Region: Ngc2264-cmentioning
confidence: 99%
See 3 more Smart Citations